Greek rational medicine : philosophy and medicine from Alcmaeon to the Alexandrians - Longrigg, James, 1934- (Routledge, 1993)
Greek Rational Medicine examines the important relationship between philosophy and medicine in ancient Greece and beyond and reveals its significance for contemporary western practice and theory.